Еxploring how demographic factors influence consumer attitudes and technology usage - Kiburu, Lydiah; Boso, Nathaniel; Njiraini, Nancy (Serbian Journal of Management, 2023)
As technology continue to define lifestyle and interactions, firms are increasingly seeking empirical evidence on how consumers’ attitudes towards technology influence technology usage. There is inadequate research from the emerging markets on the extent to which demographic factors influence the relationship between consumer attitudes and technology usage. This study therefore addressed this gap by using data from mobile banking users in Kenya to test the moderating role of education levels, age, levels of income and gender. Kenya was preferred study context because of the high penetration and levels of mobile technology usage. Results show that only education levels had statistically significant influence. Theoretical and consumer management implications as well as avenues for additional research are discussed. The study discusses the implications of the study from a theoretical, empirical, policy and industry practice perspective. Future research directions are also recommended.